ESP TALABALARINING TIL O`RGANISHIDA TALAFFUZ HATOLARI (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article provides information on pronunciation errors of esp students learning the language and explains them based on examples